Seismic resistant rocking coupled walls with innovative Resilient Slip Friction (RSF) joints. (February 2017) - Hashemi, Ashkan; Zarnani, Pouyan; Masoudnia, Reza; Quenneville, Pierre
Abstract: Multi-story hybrid timber-steel structures are becoming progressively desirable owing to their aesthetic and environmental benefits and also to the relatively higher strength to weight ratio of timber. Moreover, there is an increasing public pressure to have low damage structural systems to minimize the destruction after severe earthquakes. A recent trend in the timber building industry is the use of cross laminated timber (CLT) wall systems. CLT is a relatively novel engineered wood based product well suited for multi-story structures. Latest research findings have shown that CLT buildings constructed with traditional steel connectors can experience high damage mainly because of stiffness degradation in the fasteners. It has been proven that friction joints can provide a perfectly elastoplastic behaviour and a stable hysteretic response. Up until now, the main disadvantage of the friction joints has been the undesirable residual displacements after an earthquake. This study presents a hybrid damage avoidant steel-timber wall system using the innovative Resilient Slip Friction (RSF) joint. The proposed system includes coupled timber walls and boundary steel column as the main lateral load resisting members. RSF joints are used as ductile links between the adjacent walls or between the walls and the steel boundary columns. The efficiency of the system has been investigated by experimental joint component tests on the RSF joint followed by reversed cyclic numeral analyses and dynamic non-linear time-history simulations on the wall system. The results confirmed that the proposed system has the potential to be recognised as an efficient lateral load resisting system. Highlights: A hybrid steel-timber seismic resilient lateral load resisting system is introduced.. It includes rocking Cross Laminated Timber (CLT) walls and Resilient Slip Friction (RSF) joints. The hysteretic behaviour of the RSF joint is experimentally investigated and a flag-shaped hysteresis was confirmed. The response of the system to quasi-static analyses and non-linear time-history simulations are presented. The introduced system represented a feasible damage avoidant solution for seismic resilient structures.